(untitled) (Revista Estudios Psicológicos, 2026)
Peer attachment patterns in the school environment may be related to how adolescents perceive sexism, understood as the identification of gender beliefs that reinforce inequalities and stereotypes. The objective of this research was to determine the relationship between peer attachment styles and the perception of sexism in adolescents. For data collection, validated Likert-type scales were used to measure the dimensions of trust, communication, and alienation (attachment), as well as the hostile and benevolent components of sexism. Due to the absence of a normal distribution in the data, non-parametric analyses were applied. The results revealed a negative, moderate, and significant correlation between both variables: a higher level of peer attachment is associated with a lower perception of sexism. Specifically, the communication and alienation dimensions showed the strongest links with sexist attitudes, while trust presented a weaker but equally significant relationship. In conclusion, strengthening affective and communicative bonds among peers is associated with more critical and less stereotyped gender perceptions, suggesting that attachment quality is a key factor in promoting more equitable social interactions during adolescence.